The idea of exclusivity in the image discourse of public representatives of choreographic art - Kovalkova, Tatiana V. (Journal of the Belarusian State University. Philology, 2021)
The managing of the subject’s public capital is an integral component of professional and personal success in the information society. The article deals with the problem of forming a personal image in the mass media. The purpose of the article is to identify the ways of language representation of the idea of exclusivity in the image discourse of public representatives of choreographic art. The achieving of this goal involves solving the following tasks: to give the definition of exclusivity, to determine the role of this characteristic in the structure of the personal image of representatives of creative professions, to identify and analyze the language means used by the image subject to represent the idea of exclusivity, to determine the vectors of realization of the idea of exclusivity in the image discourse of representatives of choreographic art, based on the classification of identified language means. It is stated that the person uses the publicity to transmit purposefully a certain idea directed to make a positive impression about the subject of image on the target audience. The author applies the method of discourse analysis to study the snippets of interviews with dancers presented in the media. The analysis reveals the ways of language representation of the idea of exclusivity in the image discourse of public representatives of choreographic art and the linguistic means aimed at representing expressiveness and emotionality.